Acute isolated sphenoid sinusitis in children: A case series and systematic review of the literature. (January 2021) - Clement, W.A.; Sooby, P.; Doherty, C.; Qayyum, N.; Irwin, G.
Abstract: Objective: This study aims to present a case series and systematic review of acute isolated sphenoid sinusitis (AISS) in children in order to better characterize clinical presentation, diagnosis, treatment, and outcomes of this condition. Data sources: Ovid MEDLINE, Pubmed, Embase, Cochrane Library, and Google Scholar. Study selection: Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Full-text, peer-reviewed journal publications from 1994 to 2020 in English; focus on acute sphenoid sinusitis; pediatric patients (<18 years of age); series with two or more children. Studies were assessed for data including demographics, presenting symptoms and signs, radiological investigations, treatment, outcomes and complications. Results: Ten studies identifying 71 patients were included. Average age at presentation was 12.0 years (range 5–17 years). M:F ratio 1:1. The most common presenting symptoms were headache (98.6%), fever (50.7%), nasal symptoms (22.5%) ocular symptoms (19.7%) and decreased level of consciousness (12.7%). Twenty patients (28.1%) had neurological signs. Twenty-three patients (32.4%) presented with headache in isolation. Unsuspected diagnosis at presentation was noted in 54.0%. Average time to initial presentation was 14.0 days (median = 5.5 days, range 1–90 days). The majority of children were treated with antibiotics (98.6%) with 31.0%, 2.8% and 2.8% also undergoing sinus surgery, revision sinus surgery and neurosurgery, respectively. Intracranial complications occurred in 16.9% of patients. Significant long term sequelae occurred in 2 children (2.8%) and one death (1.4%) was also reported. Limitations: All studies were retrospective case note reviews. Conclusions: Acute sphenoid sinusitis is a rare and difficult condition to diagnose in children. The majority of patients make a full recovery with appropriate treatment. If treatment is delayed however consequences can be life-threatening.